Identifying patients with malignant spinal cord compression (MSCC) near end of life who can benefit from palliative radiotherapy - Dirk Rades; Barbara Segedin; Steven E. Schild; Darejan Lomidze; Theo Veninga; Jon Cacicedo (Radiation Oncology, 2022)
Abstract Background A previous score predicted death ≤ 2 months following radiotherapy for MSCC. For patients with a high probability of early death, best supportive care was recommended. However, some of these patients may benefit from radiotherapy regarding preservation or improvement of motor function. To identify these patients, an additional score was developed. Methods Pre-treatment factors plus radiotherapy regimen were retrospectively evaluated for successful treatment (improved motor function or remaining ambulatory without aid) and post-treatment ambulatory status in 545 patients who died ≤ 2 months. Factors included age, interval from tumor diagnosis until MSCC, visceral metastases, further bone metastases, primary tumor type, sex, time developing motor deficits, pre-treatment ambulatory status, and number of affected vertebrae. Factors significant on both multivariable analyses were included in the score (worse outcomes 0 points, better outcomes 1 point). Results On multivariable analyses, myeloma/lymphoma, time developing motor deficits > 14 days, and pre-treatment ambulatory status were significantly associated with both successful treatment and ambulatory status, affection of 1–2 vertebrae with successful treatment only. On univariable analyses, 1 × 8 and 5 × 4 Gy were not inferior to 5 × 5 Gy and longer-course regimens. Considering the three factors significant for both endpoints, three groups were designed (0, 1, 2–3 points) with treatment success rates of 4%, 15% and 39%, respectively (p < 0.0001), and post-treatment ambulatory rates of 4%, 43% and 86%, respectively (p < 0.0001). Conclusion This score helps identify patients with MSCC who appear to benefit from palliative radiotherapy in terms of improved motor function or remaining ambulatory in spite of being near end of life.